Determining How X-ray Binary Populations Vary Through Time - Antoniou, Vallia; Anastasopoulou, K.; Andrews, Jeff; Drake, Jeremy J.; Fabbiano, Giuseppina; Hatzidimitriou, Despina; Hong, Jae Sub; Kouroumpatzakis, Konstantinos; Kovlakas, Konstantinos; Maccarone, Thomas J.; Maravelias, Grigoris; Sasaki, Manami; et al. (HST Proposal, 2019)
We propose 200 ks total ACIS-S observations of the spiral galaxy NGC 2336, one of the most actively star-forming galaxies in the local Universe. The proposed observations will reach Lx 7 x 10^{37} erg/s, yielding over 40 high-mass X-ray binaries (XRBs). Archival UV data and supporting Hubble Space Telescope observations fully leverage our proposed Chandra observations by allowing us to: (a) measure the age and metallicity distribution of young XRBs; (b) measure the formation efficiency of young XRBs as a function of the age of their parent stellar populations; (c) constrain XRB formation models; (d) characterize the ultra-luminous XRB population; (e) explore the role of star formation in energizing the ISM; and (f) identify the nature of the nuclear source.